Research on the carbon emissions reduction effects of China’s digital economy: moderating role of the national big data comprehensive pilot zone policy - Xu, Weicheng; Wan, Wenqi (Frontiers in Environmental Science, 2025)
The rapid expansion of the digital economy presents substantial opportunities for achieving the “dual carbon” objectives in China and globally. Understanding how the digital economy contributes to carbon emission reduction is essential for promoting high-quality economic growth. This study examines the mechanisms through which the digital economy affects carbon emissions, with a focus on the “production side” of the social reproduction process. Using panel data from 30 provincial-level regions in China between 2012 and 2022, this study employs a dual fixed-effects model and a mediation effect model to analyze the impact of the digital economy on carbon emissions. It explores three key channels–scale effects, structural effects, and technological effects. Additionally, a moderating effect model is applied to assess the role of the National Big Data Comprehensive Pilot Zone (NBDCPZ) policy in enhancing the carbon reduction effects of the digital economy. The findings indicate that: (1) The digital economy plays a significant role in reducing carbon emissions, with its effects being more pronounced in eastern regions and areas with abundant energy resources and higher levels of digital economic development. (2) On the production side, technological progress and structural upgrading mediate the reduction of carbon emissions, whereas scale expansion increases emissions. However, the combined effect of technological progress and structural upgrading outweighs the negative impact of scale expansion. (3) The moderating effect analysis reveals that the NBDCPZ policy amplifies the carbon reduction effects of the digital economy, further strengthening its prohibitive influence on emissions. As nations increasingly prioritize sustainable development, this study provides valuable insights into the mechanisms by which the digital economy contributes to emission reduction. The findings highlight the need for region-specific policies that leverage digital transformation to achieve carbon neutrality goals.